MENINGKATKAN KEMAMPUAN BERHITUNG PERMULAAN MELALUI MEDIA CELEMEK HITUNG (Penelitian Tindakan pada Anak Usia 4-5 Tahun di TK Sekar Sari Pulomerak Cilegon Banten) - Novalta Dwi Ambarini (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2016)
The purpose of this study were (1) to know the process of implementing Media Celemek count in improving numeracy skills of children aged 4-5 years beginning in TK Sekar Sari Pulomerak Cilegon Banten; (2) the improvement of numeracy starters children aged 4-5 years in TK Sekar Sari Pulomerak Cilegon Banten after the action up media aprons count. The method used in this research is the research actions conducted in two cycles, each cycle consisting of 8 times the action disklus I and 2 times the action cycled II with 70% success criteria action. Subjects of this study were 18 children aged 4-5 years consisting of 11 boys and 7 girls. Data collection technique through observation, interviews, field notes, and documentation. The data were analyzed using the analysis of qualitative and quantitative data. Based on data analysis research and discussion, the result that: (1) the process of implementing media apron count includes three stages, namely the preparatory stage, the stage of implementation, and evaluation stage; (2) after being given an action using aprons media count to increase numeracy skills of children starters result that the first cycle reaches 45% and cycle II increased to 74%. It can be concluded that the Media Celemek can count improve the numeracy skills of children aged 4-5 years beginning in TK Sekar Sari Pulomerak Cilegon Banten.